Optimal Thermal Treatment for Effective Copper Recovery in Waste Printed Circuit Boards by Physical Separation: Influence of Temperature and Gas - Boram Kim (MDPI AG, 2021)
Printed circuit boards (PCBs) are difficult to recycle because of the layered structure of non-metal (i.e., epoxy resin, glass fiber) and copper. In this work, we conducted a systematic investigation to effectively recover copper from PCB. A thermal treatment was employed for improving the crushing performance of PCB and conducted by varying the temperature and the gas. Then, the mechanical strength, degree of liberation (DL), and copper separation efficiency of the heat-treated and untreated PCBs were investigated. After heat treatment under a 300 °C air atmosphere, the mechanical strength of PCB decreased from 386.36 to 24.26 MPa, and copper liberation improved from 9.3% to 100% in the size range of a coarser size fraction (>1400 μm). Accordingly, when electrostatic separations were performed under these conditions, a high-Cu-grade concentrate and high recovery could be obtained. The results show that the change in the physical properties of the PCBs leads to an improvement in the DL following thermal decomposition at 300 °C in air. Our study elucidates the physical properties of PCBs and the DL under various heat treatment conditions. Furthermore, it shows that the heat treatment condition of 300 °C in air is ideal for recovering copper from the PCB.